1999
DOI: 10.1071/s97112
|View full text |Cite
|
Sign up to set email alerts
|

Polymer effects on surface mechanical strength of a crusting loessial soil

Abstract: Addition of synthetic polymers to crusting soils generally improves seedling emergence and this is thought to be caused by lower mechanical strength of the crusted soil surfaces. The objective of the present study was to evaluate the mechanism by which polymer addition contributes to the reduction in crust mechanical strength. Three polymers were used, 2 anionic polyacrylamides differing in their molecular weight, and a cationic polysaccharide. Samples of a silty loam calcareous loess (Calcic Haploxeralf) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The the soil beneath. Variations and extensions of this basic observed thin seals in fact represent much thicker disturbed layers, where the unobserved remaining disapproach were suggested in a series of studies on infiltraturbed part can still affect the hydraulic properties of tion through sealed soils with constant seal properties the initial soil and, consequently, the flow processes in (Ahuja, 1974(Ahuja, , 1983Moore, 1981a;Parlange et al, 1984). the upper soil layer.…”
Section: During Seal Formationmentioning
confidence: 91%
See 2 more Smart Citations
“…The the soil beneath. Variations and extensions of this basic observed thin seals in fact represent much thicker disturbed layers, where the unobserved remaining disapproach were suggested in a series of studies on infiltraturbed part can still affect the hydraulic properties of tion through sealed soils with constant seal properties the initial soil and, consequently, the flow processes in (Ahuja, 1974(Ahuja, , 1983Moore, 1981a;Parlange et al, 1984). the upper soil layer.…”
Section: During Seal Formationmentioning
confidence: 91%
“…The maximal value measured by Eigel and applied in a series of studies dealing with infiltration Moore (1983) was 1.85 g cm Ϫ3 . Roth (1997) measured into sealed soils (Ahuja, 1983; Brakensiek and Rawls, maximal values of 1.78 to 1.91 g cm Ϫ3 for soils with silty sand, loamy sand, or sandy loam textures and values of 1983;Parlange et al, 1984;Vandevaere et al, 1998). Mualem and Assouline (1989) introduced a new con-1.44 to 1.65 g cm Ϫ3 for loess soils.…”
Section: Conceptual Models Of the Seal Layermentioning
confidence: 99%
See 1 more Smart Citation
“…In Australia, water-soluble PAMs are being marketed for use in center pivots on coarse sands as a water and nutrient conservation tool. Levy and Rapp (1999) reported that water-soluble PAM, applied to the surface of a silt loam soil, reduced the loss of water during the drying process.…”
Section: Infiltrationmentioning
confidence: 99%
“…Therefore, it is possible to evaluate the sensitivity of the modeled infiltration to changes in τ resulting from treatments that affect soil stability. These treatments can address physical soil properties, like the initial water content of the soil surface (Le Bissonnais and Singer, 1992), or the chemical conditions of the soil water system (Shainberg, 1992; Levy and Rapp, 1998).…”
Section: Modeling Flow Processes In Sealed Soils and During Seal Formmentioning
confidence: 99%